Integrated berth allocation and quay crane assignment with maintenance activities - Zheng, Feifeng; Li, Ying; Chu, Feng; Liu, Ming; Xu, Yinfeng (International journal of production research, 2019)
With the rapid development of worldwide container trade, quay cranes and other resources in container terminals are suffering from increasing workloads. To reduce their failure probabilities, quay cranes usually require preventive maintenance. However, these important activities are often ignored during quay crane planning in literature. This work studies an integrated berth allocation, quay crane assignment and specific quay crane assignment problem where quay crane maintenance is involved, and establishes an integer linear programming with the objective of minimising the total turnaround time. Due to the NP-hardness of the problem, CPLEX only solves instances with up to 18 vessels. For solving larger instances, we propose Left-and-Right Vessel Move (LRVM) algorithm and improved Genetic Algorithm (GA). Experimental results reveal that GA slightly outperforms LRVM with respect to solution quality as the solution of LRVM serves as one of the initial chromosomes of GA. LRVM can output feasible solutions within seconds, even for instances with 50 vessels. We further present a sensitivity analysis of preferred berth segments, and make numerical comparison on algorithm performance for the relevant model without quay crane maintenance. Both the models and proposed heuristics in this work help in dealing with the operational management of container terminal resources in practice.